Functional Molecular Silicon Compounds II Low Oxidation States - Scheschkewitz, David.; Scheschkewitz, David. (Structure and Bonding,, 2014)
Carsten Präsang and David Scheschkewitz Silyl Anions Masafumi Unno Substituted Polyhedral Silicon and Germanium Clusters Burgert Blom and Matthias Driess Recent Advances in Silylene Chemistry: Small Molecule Activation En-Route Towards Metal-Free Catalysis Takeaki Iwamoto and Shintaro Ishida Multiple Bonds with Silicon: Recent Advances in Synthesis, Structure, and Functions of Stable Disilenes Eric Rivard Recent Advances in the N-Heterocyclic Carbene-Supported Chemistry of Silicon.